(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2007)
Country made liquors are consumed in both rural and urban areas of India. Twenty-five Countries made liquor samples were collected at random from National capital territory of Delhi. All these samples were analyzed for physical properties and alcohol content by Gas liquid chromatography in Toxicology Laboratory of Department of Forensic Medicine and Toxicology, AIIMS, New Delhi. The mean ethyl alcohol content was 32.88 %V/V (6.70 -96.61%V/V). No evidence of methyl alcohol was found in any of the samples. The mean Proof was 56.832(43.8-75)0. The Mean PH was 7.1 (4.0 – 8.5). 22 samples were Carmel in color and rest 3 was colorless. All samples were having strong burning taste and characterstic, but weak smell. 3 samples were sealed in polythene pouch, 2 in Plastic bottle and 20 in glass bottle. One sample was looking turbid and rests were clear.